The Use of Closed Incision Negative-Pressure Wound Therapy in Orthopaedic Surgery. Issue 9 (1st May 2018) - Nam, Denis; Sershon, Robert A.; Levine, Brett R.; Della Valle, Craig J.
Abstract : Wound complications and surgical site infections after orthopaedic procedures result in substantial morbidity and costs. Traditional postoperative wound care consists of applying sterile, dry gauze and abdominal pads to the surgical site, with more frequent dressing changes performed in cases in which wound drainage is excessive. Persistent incisional drainage is of particular concern because it increases the risk of deep infection. The use of closed incision negative-pressure wound therapy (ciNPWT) to manage delayed wound healing was first reported a decade ago, and the benefits of this treatment modality include wound contraction with diminished tensile forces, stabilization of the wound environment, decreased edema and improved removal of exudate, and increased blood and lymphatic flow. Numerous trauma, plastic surgery, and general surgery studies have demonstrated that ciNPWT improves wound healing. In orthopaedic surgery, ciNPWT has been shown to be clinically effective for incisions at high risk for perioperative complications. However, specific indications for ciNPWT continue to be defined.